When climate justice goes wrong: Maladaptation and deep co-production in transformative environmental science and policy. (October 2022) - Forsyth, Tim; McDermott, Constance L.
Abstract: Maladaptation to climate change is often portrayed as arising from the unjust exclusion of vulnerable people. In turn, analysts have proposed knowledge co-production with marginalized groups as a form of transformative climate justice. This paper argues instead that maladaptation arises from a much deeper exclusion based upon the projection of inappropriate understandings of risk and social identity that are treated as unquestioned circumstances of justice. Drawing on social studies of science, the paper argues that the focus on co-production as an intentional act of inclusion needs to be considered alongside "deep" or "reflexive" co-production, which instead refers to the non-cognitive and unavoidable simultaneous generation of knowledge and social order. These processes have linked visions of planetary justice with an understanding of climate risk based on global atmospheric change, and an assumption that community forms an antidote to individualism. The paper uses a discussion of adaptation in western Nepal to illustrate how such deep forms of co-production have significantly reduced understandings of "what" adaptation is for, and "who" is included. Maladaptation, therefore, is not simply unjust implementations of an essentially fair model of adaptation, but also the allocation of exclusionary visions of what and for whom adaptation is for. Debates about transformative climate justice therefore need to understand how their critiques of classical liberal justice generate exclusions of their own, and to engage vulnerable people in reframing, rather than just receiving, circumstances of justice. There is also a need to examine how these circumstances remain unchallenged within environmental science and policy. Highlights: Maladaptation arises from inappropriate frameworks of climate risk and social identity. Deep co-production analyses how circumstances of justice become unquestioned. Transformative climate justice requires reframing, not only applying, circumstances of justice. The example of Nepal shows how adaptation has avoided certain forms of vulnerability.